Pricing in Consumer Digital Markets: A Dynamic Framework. Issue 3 (August 2019) - Reisman, Richard; Payne, Adrian; Frow, Pennie
Supplier firms are increasingly seeking new ways to personalize their offers and differentiate their products, especially in contested digital markets. One approach that shows promise involves encouraging customers to participate in pricing decisions using schemes such as "pay-what-you-want" where the customer has an input into determining the price. These approaches can benefit both the customer in terms of paying a reasonable price and reducing risk, and the supplier in terms of increasing sales and generating deep customer insights that can assist in relationship development. However, extant research shows limitations associated with these pricing approaches and, despite some qualified successes, there has not been widespread adoption in businesses. This study extends consideration of existing participative pricing schemes and proposes a new conceptual framework, termed FairPay. This framework overcomes many of the limitations of previous approaches, while addressing important challenges, especially those faced by many digital product suppliers. The framework offers an attractive pricing solution for both customers and suppliers, ensuring an equitable exchange that is based on value-in-use. We discuss the application of this framework in the context of digital products, where the approach has special promise.